INTRODUCING MAKLUM - THE GENERAL REFERENCE EXPERT ADVISER DEVELOPED FOR A UNIVERSITY LIBRARY - Awang Ngah, Zainab; Mohd. Zaid, Nor Eliza; Awang Ngah, Zainab; Mohd. Zaid, Nor Eliza (Malaysian Journal of Library and Information Science, 2017)
Describes the development of a standalone expert system called MAKLUM which aims to provide answers to general reference enquiries relating to library facilities, services, regulations, loans, membership, location of items, public amenities, etc. The Adviser is developed for the main library of the University of Malaya using the expert system shell, CRYSTAL 4.50. The system can run from any personal computer with DOS. Fifteen undergraduates tested the system, out of whom 73% rated the Adviser as very good, excellent, and 84% liked most the system’s ease of use and its user interface. Information about library services, facilities, borrowings and reference privileges are the mostly sought after by the undergraduates.